Interactions et films de classe pour réfléchir la formation à l’enseignement des Mathématiques en Français langue seconde. Décrire pour mieux former ? - Cécile Sabatier; Danièle Moore; Nathalie Sinclair (Recherches en didactique des langues et des cultures)
Using classroom videos, this paper offers an analysis of the interactions between a teacher and her students to illustrate how this teacher creates the didactic conditions for the learning of geometric knowledge. The context is a grade two French immersion students in British Columbia (Canada). By crossing a didactics of language perspective with a disciplinary didactic perspective, and with the goal of supporting teacher education, we use classroom observations to inquire into the pertinence of an approach to teacher education where the didactics of mathematics and the didactics of language are taken to be juxtaposed, rather than integrated, particularly in a context where the teacher is French as a second language within a predominantly anglophone and plurilingual environment.